A Case of Massive Hepatic Infarction in a Patient with HELLP Syndrome - Jessica Morgan; Micaela Della Torre; Anna R. Whelan; Sophia M. Rodriguez; Laura M. DiGiovanni (Thieme Medical Publishers, Inc., 2019)
Abstract Background Hepatic infarction is an exceedingly rare complication of hemolysis, elevated liver enzymes, and low platelets syndrome. Few cases have been described in the medical literature and the true incidence remains unknown. It can lead to fulminant liver failure, liver transplant, or death if not promptly addressed. Case Report A 22-year-old primigravida presented with right upper quadrant and epigastric pain at 28 weeks' gestation. She had severely elevated blood pressures requiring intravenous antihypertensives as well as proteinuria, thrombocytopenia, and mild transaminitis. Within 6 hours of admission, her rapidly rising liver function tests (LFTs) necessitated urgent delivery by primary cesarean section. Her liver enzymes continued to rapidly worsen postoperatively and immediate postpartum computed tomography of the abdomen and pelvis revealed massive hepatic infarction, 11 × 10 × 15 cm, of the right lobe of the liver. Her transaminases peaked at alanine transferase of 2,863 IU/L and aspartate transferase of 2,732 IU/L. She received supportive multidisciplinary intensive care, and LFTs returned to normal by postoperative day 20. Conclusion Hepatic infarction is an extraordinarily rare complication of pre-eclampsia. Early recognition and prompt multidisciplinary management are vital to prevent catastrophic bleeding, hepatic failure, and death.